Dividend Price Ratio and Stock Return: Evidence from Pakistan, India and China - Baloch, Shazia; Hafeez, Muhammad; Maeenuddin; Ahmad, Ashfaq; Javed, Asma (International Journal of Psychosocial Rehabilitation, 2020)
This study estimated the effect of dividend premium and size in the growing capitalization markets of Pakistan, India, and China. This paper examined the role of dividend in the terms of large and small firms and to correlate the dividend with stock returns. This study used monthly closing prices of 40 non-financial sector firms listed at Karachi Stock Exchange (KSE) for Pakistan, 40 from the Taiwan Economic Journal Database (TEJ) for China, and 40 from the Bombay Stock Exchange (BSE) for India for the period of 2004 to 2014 based on market capitalization. Descriptive statistics and correlation analysis have been used to examine the relationship between the independent variables market premium (MKT), size premium (SMB), dividend premium (LMH), and dependent variable stock return. Results from the descriptive statistics of Fama and French three factors show that Pakistan has the highest mean value of marke premium and dividend premium, while India has the highest mean value of size premium. Results of standard deviation show that India has the lowest value of standard deviation of market premium and size premium, while China has the lowest value of SD for dividend premium. As per the results of the correlation analysis, Pakistan has the strongest negative relationship between dividend premium (LMH) and market premium (MKT), between dividend premium and size premium, and between size premium and market premium as compared to India and China. The results revealed the positive relationship between stock returns and dividends in the rapidly growing markets of Pakistan, India, and China. From the overall results, we concluded and suggest that strategies of investment would be schemed by the investors on the basis of the size, market premium, and dividend premium. The consequences of the study disclosed the positive relationship between stock returns and dividends in the rapidly growing markets of Pakistan, India, and China.